Table of Content - - (Journal of Curriculum and Teaching Methodology, 2024)
Table of Content 1. A training program based on the SWOM model, in developing creative teaching skills with students of the Islamic Studies Curriculum Department at the College of Education, Sana’a Dr. Abdul-Rahman Qaid Abdullah Al-Yusufi, Prof. Abdul-Salam Abdo Qasim Al-Mekhlafi 2. The Reality of Using Blended Learning in the Arab East Colleges from the Point of View of Faculty Members Ms. Mahasin Hussain Theqah, Co-Prof. Dalia Nabil Al-Manhrawi 3. Teaching of Non- Linguistic Disciplines (NLD) in Secondary school in Morocco: Reference, organizational, pedagogical and procedural requirements towards improving learning Accredited Lecturer Youssef EL GUAMRI, Accredited Lecturer Omar AMAHMID, Associate Professor Youness RAKIBI, Associate Professor Abdelhalim FAKIHANI, Accredited Lecturer Mohamed YAZIDI, Accredited Lecturer Bouchra RAZOKI, Accredited Lecturer Khaidija KAID RASSOU, Lecturer Saadia OUIZAT , Accredited Lecturer Ouafae SERRAR 4. The Extent of Future Thinking Skills Inclusion in Digital Skills Course for the Fourth Grade of Elementary Schools in the Kingdom of Saudi Arabia Ms. Amani Muneer Alnufaei, Prof. Najwa Atyan Almohammadi 5. The Impact of Project-Based Learning Using a STEM Approach on Developing Entrepreneurship Skills Among High School Female Students in Digital Technology (2-2) Ms. Nuriyyah Naser Adullah Almoafa 6. Reasons for Weak Reading Skills in English among Elementary School Students from the Perspective of English Teachers in Elementary Schools in Riyadh Ms. Shamma Sulimsn Aljurijeer 7. The effectiveness of training fourth grade students on mental arithmetic strategies in improving their performance in finding the results of arithmetic operations on numbers Ms. Anwaar Sulaiman Ali Al-Maqbali, Ms. Hamida Hamid Khalfan Al-Mufarji